Il ciclo tecnologico dell’odontotecnico e i risultati della pre-mappatura dei disagi e dei pericoli / Prosthodontics technological processes and results of risk profiling - Giambartolomei, M.; Bolognini, P. (La Medicina del Lavoro, 2011)
«Prosthodontics technological processes and results of risk profiling». Background: In prosthodontics laboratories, dental devices and appliances are made to measure, optimized and tested, in particular prostheses, following the design  specifications of the dentist. Objective: he purpose of this study was to learn about and become familiar with  the work processes in prosthodontics laboratories and also analyze inconveniences and risks in the laboratory work space. Methods: The simple computerized pre-mapping model, the risk profiling method, was used. Repetitive movement evaluation was further analyzed using the multitask OCRA mini-checklist. Results: repeated movement risk to the upper limbs was identified during some production processes; chemical and physical pollutants were present as well as problems related to the use of certain equipment. Conclusions: This by no means exhaustive analysis can be considered as a starting point in creating guidelines in risk evaluation in a sector consisting of small and very small businesses which has so far not been  studied in depth.